Digitalization of Education During the COVID-19 Pandemic: A View From The Functional Structural Theory Perspective - Sarah, Nursani (Jurnal Pendidikan Ilmu Sosial, 2022)
The Covid-19 pandemic is affecting education as well.The virtual meeting at home replaced the face-to-face learning system at school or campus prior to the pandemic.In order to continue learning, this is done.The purpose of this research is to investigate the digitalization of education from Talcott Parsons' Structural Functional Sociology theory.A literature review approach is combined with qualitative research in this study.The study's findings demonstrate that the AGIL function of Talcott Parsons' structural functional theory is used to examine changes in the pandemic's learning system:1) Modification:Face-to-face learning systems are transferred to homes via online or virtual meetings.2) Goal Attainment is an online learning system that lets students learn and teach even when the COVID-19 pandemic is going on. It is done so that students can still exercise their right to education and use it to the fullest.3) In order to integrate, governments, particularly the Ministry of Education and Culture, and relevant schools must work together to develop policies that can support students and online learners. One such policy is internet quota assistance for Indonesian students.4) Despite the fact that learning does not take place in classrooms or campuses, latency requires teachers and students to uphold the values of discipline that are determined.